The Implementation of Al-Adab Al-Ijtima’i Style in Buya Hamka’s Interpretation (Study of Fahisyah Verses) - Ummi Tsaqila; Saifullah Saifullah; Afrizal Nur; Khairunnas Jamal (Jurnal An-Nur, 2022)
This articel examines the fahisyah verses in the Qur'an. Fahisyah is a heinous or ugly act. Where several terms refer to the various meanings of spectacle, one of which is the term fahisyah which has the meaning of horrific deeds in the Qur'an. According to the view of human reason, the word fahisyah and its derivation has the meaning of any form of toxicity or sin that is seen as very bad. At the same time, this deed can affect others and is a worse deed than al-su'. This research uses the interpretation of Buya Hamka's Tafseer al-Azhar, which is the primary source of this articel. The method used in writing this research is to use the library research method, namely by looking for data from various literature and references related to the problems above. The approach used is a thematic engineering approach, namely by explaining things related to the meaning of the word fahisyah to be analyzed according to the style of interpretation of the interpretation, namely the pattern of Adabi al-Ijtima'i which is social. As for the implementation of the Adabi al-Ijtima'i style to the fahisyah verses according to Buya Hamka, which has been analyzed based on its indicators, namely, the relationship of interpretation with the social life of the community in surah al-Isra' verse 32 that there will arise dangerous diseases and damage the offspring caused by adultery, namely syphilis and gonorrhea diseases. There is an interpretation of the verse about the risks or adverse effects of these heinous acts mentioned by Buya Hamka in his interpretation, which shows the problems and relationships of interpretation with the community's social life, which is also a warning to stay away from these heinous deedsTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//